Reconciling critical zone science with ecosystem and soil science—a personal-scientist perspective - Lohse, Kathleen A. (Frontiers in Water, 2023)
The critical zone has been the subject of much discussion and debate as a term in the ecosystem, soil and earth system science communities, and there is a need to reconcile how this term is used within these disciplines. I suggest that much like watershed and soil ecosystems, the critical zone is an ecosystem and is defined by deeper spatial and temporal boundaries to study its structure and function. Critical zone science, however, expands the scope of ecosystem and soil science and more fully embraces the integration of earth sciences, ecology, and hydrology to understand key mechanisms driving critical zone functions in a place-based setting. This integration of multiple perspectives and expertise is imperative to make new discoveries at the interface of these disciplines. I offer solid examples highlighting how critical zone science as an integrative science contributes to ecosystem and soil sciences and exemplify this emerging field.